ARVI treatment in children - L. V. Nikitina (Лечащий Врач, 2021)
Acute respiratory viral infections is a pressing problem of pediatrics. ARVI treatment includes prescription of etiotropic and symptomatic therapy. Fever is a defense reaction against the infectious agent. The pediatrician’s arsenal traditionally includes paracetamol and ibuprofen as antipyretic therapy. The article covers the studies which confirm efficiency of use of the bioregulation drug compared to the efficiency of paracetamol.